Oral Health status and its impact on performances of the members of the Air Force based in the Western Province - Abeyruwan, P.S (My University, 2004)
This was a cross sectional descriptive study. A total of 663 Air Force personnel (median age 27 years) were selected using systematic sampling technique. Oral health status of the subjects was assessed by using DMFT and CPITN indices according to WHO standard criteria and methods. Prevalence of caries was found to be 82.4 percent with mean DMFT 4.2 teeth and It was positively associated with age (PO.OOl) while officers having significantly low prevalence of caries (pO.05) Perceived oral health status, perceived treatment need and utilization of oral health care services associated significantly with mean DMFT of the sample (PO.OOl). Prevalence of healthy gingival status was 17.9 percent and it was found to be high among - 27 years, females and people with low educational level (pO.05). Substantial number (16.1 percent ) stated that their oral condition had affected their daily performances. Most frequently affected function was difficulty in cleaning teeth (5.1percent ) while absence from work (0.02 percent ) due to oral condition is the least reported impact Gender and service experience had influenced the impact of oral health significantly (p0.05). Overall impact was significantly influenced by the DMFT (pO.OOI) while gingival condition had not influenced the impact of oral health significantly. Coping to the general population of Sri Lanka, low prevalence of caries and gingival disease conditions year observed among the Air Force personnel. However frequency of reporting impacts due to oral health status was comparably high among this group